How Should Historical Reenactment Be Used in History Teaching? - Neval Akça Berk (Sakarya University, 2013)
The main purpose of this study is to determine the steps to apply the historical reenactment in the history course based on the examples used in education and to present this field of application to the history teachers by discussing the utilities and the limitations of applying the activity in question in history course. The study is in the descriptive survey model. It becomes difficult for the students living in the twenty first century to understand and to interpret the people having lived in the past because they had different traditions, attitudes and values. Therefore, using the applications related to historical reenactment in history teaching makes it possible to bring the past to the modern day. Historical reenactment is always used differently by both voluntary organizations independently and the teachers in schools in many countries. In our country it is used by various organizations except for pedagogical purposes but it is rarely seen in history teaching. If the history teachers in Turkey use the applications of historical reenactment, the use of historical reenactment will be common and be enhanced with different practices.